2000
DOI: 10.1177/014920630002600104
|View full text |Cite
|
Sign up to set email alerts
|

Jackson and Schuler (1985) Revisited: A Meta-Analysis of the Relationships Between Role Ambiguity, Role Conflict, and Job Performance

Abstract: We conducted a meta-analysis of correlations between role ambiguity and job performance and role conflict and job performance. Previous meta-analyses of these role constructs and performance relationships (e.g., Jackson & Schuler, 1985) were limited by small sample sizes and sparse reporting of reliability estimates in primary studies. The present study used a comprehensive database with a larger sample size and a distribution of interrater reliabilities to extend the previous findings. We also tested mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
481
6
27

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 487 publications
(544 citation statements)
references
References 27 publications
30
481
6
27
Order By: Relevance
“…In addition, our study and that of Tubre and Collins (2000) found comparable meta correlations of role ambiguity with self-rated performance, with ρ = −.30, −.28, respectively, and of role ambiguity with supervisor-rated performance, with ρ = -.16, -.20, respectively. The similarity could be related to the fairly large number of samples used in the two studies for these effect sizes.…”
Section: Reconciling Our Results With Previous Analytical Reviewssupporting
confidence: 78%
See 2 more Smart Citations
“…In addition, our study and that of Tubre and Collins (2000) found comparable meta correlations of role ambiguity with self-rated performance, with ρ = −.30, −.28, respectively, and of role ambiguity with supervisor-rated performance, with ρ = -.16, -.20, respectively. The similarity could be related to the fairly large number of samples used in the two studies for these effect sizes.…”
Section: Reconciling Our Results With Previous Analytical Reviewssupporting
confidence: 78%
“…The results of our study for the meta correlation of role ambiguity and general performance were similar to those of Tubre and Collins (2000), with ρ = −.24, −.21, respectively. In addition, our study and that of Tubre and Collins (2000) found comparable meta correlations of role ambiguity with self-rated performance, with ρ = −.30, −.28, respectively, and of role ambiguity with supervisor-rated performance, with ρ = -.16, -.20, respectively.…”
Section: Reconciling Our Results With Previous Analytical Reviewssupporting
confidence: 73%
See 1 more Smart Citation
“…Because organizations are role systems in which the social interactions between system members determine how work is carried out (Katz and Kahn 1978), role conflict should impact performance outcomes (Tubre and Collins 2000). Therefore, we investigate how role conflict among MMs is related to strategic renewal activities within their units.…”
Section: Role Conflict and Exploratory Innovationmentioning
confidence: 99%
“…Role tension results from unclear or conflicting expectations for a specific role (Kahn, Wolfe, Quinn, Snoek, & Rosenthal, 1964), and role tension predicts work-related behaviors and attitudes (Eatough, Chang, Miloslavic, & Johnson, 2011;Örtqvist & Wincent, 2006;Tubré & Collins, 2000;Wincent & Örtqvist, 2009). Given that (1) passion might relate to role opportunity and (2) the link between role tension and subsequent behaviors and attitudes, it is of great interest to link passion to role tension.…”
Section: Introductionmentioning
confidence: 99%